Comparison of progesterone and glucocorticoid receptor binding and stimulation of gene expression by progesterone, 17-alpha hydroxyprogesterone caproate (17-OHPC), and related progestins - Attardi, Barbara J. (2007)
CONDENSATION: 17-hydroxyprogesterone caproate is not better than progesterone in binding to progesterone or glucocorticoid receptors or eliciting gene expression in progesterone responsive genes. Comparison of progesterone and glucocorticoid receptor binding and stimulation of gene expression by progesterone, 17-alpha hydroxyprogesterone caproate (17-OHPC), and related progestins. OBJECTIVE: To determine whether the reduction in premature birth attributable to 17-OHPC occurs because of a greater affinity for progesterone (PR) or glucocorticoid (GR) receptors or by enhanced stimulation of progestogen responsive genes when compared with progesterone. STUDY DESIGN: We performed competitive steroid hormone receptor binding assays using cytosols expressing either recombinant human PR-A (rhPR-A) or B (rhPR-B) or rabbit uterine or thymic cytosols. We used four different carcinoma cell lines to assess transactivation of reporter genes or induction of alkaline phosphatase. RESULTS: Relative binding affinity of 17-OHPC for rhPR-B, rhPR-A and rabbit PR was 26–30% that of progesterone. Binding of progesterone to rabbit thymic GR was weak. 17-OHPC was comparable to progesterone in eliciting gene expression in all cell lines studied. CONCLUSIONS: Binding to PR, GR or expression of progesterone-responsive genes is no greater with 17-OHPC than with progesterone. Other mechanisms must account for the beneficial effect of 17-OHPC on preterm birth rates.